Factors Affecting the Learning Process of Professionals in Architectural Design Firms - Barlak, Ozturk; Arditi, D; Gunaydin, H.M.; Kale, S.; Yitmen, İbrahim (My University, 2009)
Learning is considered to be a sophisticated process and a source of competitive advantage. Learning is essential in project-based environments. The one-of-a-kind structure of the operations of architectural design firms triggers special learning needs and requires a continuous learning activity. Learning is considered to improve an architectural design firm’s efficiency by recognizing the role of individuals in enhancing the firm’s objectives. However, theoretical research on individual professionals’ learning process in the architectural design is rather uncommon. The process of individual learning is composed of (1) data acquisition (2) assessment of the acquired information and (3) implementation of the knowledge gained in a group setting. Ten factors were identified to assess the effectiveness of the learning processes of professionals. This study is the first study in the field of architecture that presents a conceptual model about the factors that affect the effectiveness of the learning process of professionals.
Keywords: Learning Process; Architectural; Design Firms